[Afisz. Incipit] Kupujemy zmarzłe ziemniaki. (Gniew : [wydawca nieznany], 1947)
Sztrajfa z ogłoszeniem.
Keywords: Gniew (Polska) -- 1945-1970 -- druki ulotne; Gniew (woj. pomorskie, pow. tczewski, gm. Gniew); Druki ulotne -- 1945-1970.; Druki ulotne